Corporate social responsibility in India : some empirical evidence - Siva Raju, S., 1954- (Springer, 2017)
Annotation This work presents the authors' recent field experiences of corporate social responsibility (CSR) activities in different regions of India. It also demonstrates how social auditing and stakeholder mapping help analyse the impact that particular individuals or groups may have on the functioning of any company in an area.
Keywords: Social responsibility of business -- India.; Industrial management -- Social aspects -- India.; India.; elektronické knihy; electronic books